HGG-04. TARGETING GABAERGIC NEURON-GLIOMA SYNAPSES IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) THROUGH ANTI-EPILEPTIC DRUG REPURPOSING. (1st June 2021) - Barron, Tara; Mehta, Vilina; Woo, Pamelyn; Monje, Michelle
Abstract: Pediatric high-grade gliomas, including diffuse intrinsic pontine glioma (DIPG), are the leading cause of brain cancer-related death in children. While enormous progress has been made in recent years for many forms of cancer, high-grade gliomas remain seemingly intractable, indicating that fundamental aspects of glioma growth are not yet sufficiently understood. Neuronal activity drives glioma growth both through paracrine signaling and through direct neuron-to-glioma synapses. Recently glutamatergic, AMPA receptor-dependent synapses were discovered between microenvironmental neurons and malignant glioma cells. The depolarizing current that results from synaptic and other forms of electrical neuron-glioma signaling promotes pediatric high-grade glioma proliferation and regulates growth. Neuron-glioma cell synapses mediated by other neurotransmitters remain largely unexplored, though glioma cells express genes encoding neurotransmitter receptors such as GABAA receptor subunits. Using whole-cell patch clamp electrophysiology in patient-derived DIPG xenografts, we have identified functional GABAergic neuron-to-glioma synapses mediated by GABAA receptors. GABAergic input has a depolarizing effect on glioma cells, but the magnitude of depolarization is heterogeneous between high-grade glioma subtypes and between patient-derived DIPG xenograft models. As membrane depolarization increases glioma proliferation, depolarizing GABAergic inputs to glioma cells could promote DIPG progression. Drugs that stimulate GABA signaling, such as benzodiazepines, are often given to pediatric glioma patients to treat nausea, seizures or anxiety. In patient-derived DIPG xenograftn models, lorazepam, a benzodiazepine that increases GABAA receptor conductance, increases glioma growth. Conversely, levetiracetam, an anti-epileptic drug that reduces synaptic transmission including at GABAergic neuron-glioma synapses, reduces glioma proliferation in patient-derived DIPG xenografts. This emerging understanding of brain cancer neurophysiology reveals new therapeutic targets and highlights commonly used drugs about which more study is required in this disease context.